Flash-less cold forging of connecting rod using computer-aided FE simulation - Khaleed, M.T.H.; Mujeebu, M.A.; Abdullah, A.B.; Irfan Anjum, Magami; Ahmed, N.J. Salman (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.